# 7x-(-1)/-8=-4 (answer)

[(7x)-(-1)]/-8= (7x+1)/-8=-4 7x+1=32 ... Cross multiplication -1 -1 (7x)/7=31/7 x=31/7 You can check this value for x by plugging it into the original equation [7*(31/7)-(-1)]/-8 (31+1)/-8 32/-8=-4 -4=-4...

WYZANT.COM
CREATE FREE ACCOUNT
Sign In

Access thousands of free resources from expert tutors

Comment on posts and interact with the authors

Ask questions and get free answers from tutors

View videos, take interactive quizzes, and more!

[(7x)-(-1)]/-8= (7x+1)/-8=-4 7x+1=32 ... Cross multiplication -1 -1 (7x)/7=31/7 x=31/7 You can check this value for x by plugging it into the original equation [7*(31/7)-(-1)]/-8 (31+1)/-8 32/-8=-4 -4=-4...

The Pythagorean theorem, a^2+b^2=c^2, is used when you are given a right triangle (a triangle with one right angle) and you are asked to find either side a, b or c (given two sides). Sides a and b are the lengths of any two of the legs (long leg or short leg) and side c represents the length...

S=p/(q+p(1-q)) by multiplying both the numerator and denominator by 1/(1-q) S=(p*(1/(1-q)))/(1/(1-q))*q+p(1-q)*(1/(1-q)) You can now cancel out common terms to get S=(p/(1-q))/(q/(1-q))+(p(1-q))/(1(1-q)) (the common denominator is(1-q) =(p/(1-q))/(q+p-pq)/(1-q) S/1=(p/(1-q))*((1-q)/(q+p-pq))...

For the problem x=8/(9x+9)=11 First, you can cross multiply. Then, you get 8=99x+99 (99x+99) comes from distributing the 11 to 9x and to 9 8=99x+99 -99 -99(subtract 99 from both sides of the equation in order to isolate...